Ageing population in Europe: The individual, the family and the welfare state - Παπαδούδης Γιώργος (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2019)
Population ageing in Europe is undeniably a success story. At the same time the new demographic mix is already challenging the old social policy framework together with a series of underlying socioeconomic factors such as inequalities and stratifications. The welfare state across Europe struggle among the current and projected total cost of ageing and the current and projected needs of an emerging ageing population. Pension, health care and long-term care systems tend to treat the needs and abilities of the older individuals as if there is no variation among them. But all individuals do not age following the same pattern. Divergent pathways over the life course present different outcomes in later life. Without innovative and targeted policy-making for the near and distant future the ageing population is in danger to be trapped between ineffective social support and inadequate family support (if any).